2022
DOI: 10.1007/s11356-022-20431-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coal rents, transportation, electricity consumption, and economic globalization on ecological footprint in the USA

Abstract: Over the last three decades, the world has been facing the phenomenon of the ecological deficit as the ecological footprint is continuously rising due to the persistent decline of the per-capita bio-capacity. Moreover, there is a substantial increase in globalization and electricity consumption for the same period, and transportation is contributing to economic prosperity at the cost of environmental sustainability. Understanding the determinants of ecological footprint is thus critical for suggesting appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…The results showed that technology adoption has a positive link with ES. These results are supported by Nathaniel, Yalçiner, and Bekun (2021); (Shah, Hussain, Nawaz, & Iqbal, 2021;Wenlong et al, 2022), which claims that the tendency of firms to adopt new technologies enables them to address and mitigate environmental issues and sustains environmental productivity. These results are also in line with the study of Jimoh and Lin (2019).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The results showed that technology adoption has a positive link with ES. These results are supported by Nathaniel, Yalçiner, and Bekun (2021); (Shah, Hussain, Nawaz, & Iqbal, 2021;Wenlong et al, 2022), which claims that the tendency of firms to adopt new technologies enables them to address and mitigate environmental issues and sustains environmental productivity. These results are also in line with the study of Jimoh and Lin (2019).…”
Section: Discussionmentioning
confidence: 82%
“…The findings proposed that a) wind power had the lowest energy consumption, less emission of carbon, and lowest possible environmental effect, b) according to an examination of ecological footprints at the provincial level, whilst the other provinces were in ecological surplus, with the majority of them having ecological areas above 50%, c) Of the three RE sources, only wind power reduced energy consumption as compared to thermal power generation, which used 1170.911 kJ/kWh. Currently, the most effective source of RE is wind power (Wenlong et al, 2022). Similarly, Apergis and Payne (2014) also worked on RE output along with ED through carbon emission.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it will not be helpful during the later stages. Wenlong et al (2023) used the ARDL approach. They discovered that coal transportation and rents both considerably and favorably contribute to the shortand long-term decline of ecological footprints at various quantile ranges.…”
Section: Non-renewable Energy Consumption and Eiwbmentioning
confidence: 99%
“…In comparison, rare studies employed the ecological footprint as a proxy for the environmental deterioration. Analyzing ecological footprint variables has become crucial for establishing environmental sustainability [37]. The effects of human activity on ecosystems have persistently worried academics over the years.…”
Section: Literaturementioning
confidence: 99%